2020
DOI: 10.21475/ajcs.20.14.02.p2557
|View full text |Cite
|
Sign up to set email alerts
|

Growth, biomass distribution, gas exchange and chlorophyll fluorescence in cowpea (Vigna unguiculata (L.) Walp.) under drought conditions

Abstract: Drought modifies plant development and generates losses in agricultural production. The aim of this study was to analyze the growth, biomass distribution, gas exchange, and chlorophyll fluorescence in nine cowpea (Vigna unguiculata) genotypes under drought conditions in the greenhouse condition. A completely randomized experimental design with four replicates was used. The following genotypes (treatments) of LC-006-016, LC-029-016, LC-036-016, LC-021-016, LC-005-016, LC-009-016, LC-014-016, LC-002-016, and Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Higher shoot height and biomass likely translates to a larger photosynthetic apparatus able to sustain higher grain yield [51]. However, in the study of Ayala et al [53], an inversed correlation between shoot development (SDW and PH) and water use efficiency was observed, suggesting that greater shoot development leads to a higher loss of water being prejudicial under drought conditions. Likewise, Iseki et al [15] also found shoot biomass to be related with plant water status, where lower shoot biomass could confer better drought tolerance.…”
Section: Screening For Drought Tolerant Genotypesmentioning
confidence: 92%
“…Higher shoot height and biomass likely translates to a larger photosynthetic apparatus able to sustain higher grain yield [51]. However, in the study of Ayala et al [53], an inversed correlation between shoot development (SDW and PH) and water use efficiency was observed, suggesting that greater shoot development leads to a higher loss of water being prejudicial under drought conditions. Likewise, Iseki et al [15] also found shoot biomass to be related with plant water status, where lower shoot biomass could confer better drought tolerance.…”
Section: Screening For Drought Tolerant Genotypesmentioning
confidence: 92%
“…Another key advantage of cowpea production is that when used as an inter-crop with other crops, it induces the growth of beneficial soil microorganisms and reduces the use of synthetic agrochemicals (Bukovsky-Reyes et al, 2019;Sun et al, 2019). In terms of importance, cowpea production contributes significantly to economic productivity and environmental sustainability in Africa (Martins et al, 2003;Olajide and Ilori, 2017;Ovalesha et al, 2017;Cardona-Ayala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars defend that the chlorophyll a fluorescence as the first stressor signal [47,60,71,72] while the production of H 2 O 2 and MDA are the stress signals, informing that the antioxidant systems are not able to cope with the ROS and the damage to the membrane phospholipids [66,73,74]. H 2 O 2 has the capacity to initiate lipid peroxidation and degrade proteins.…”
Section: Discussionmentioning
confidence: 99%